Pengaruh Jarak Waktu Pemberian Pakan Konsentrat dan Hijauan Terhadap Produktivitas Kambing Peranakan Etawah Lepas Sapih - Iswoyo, Iswoyo; Widianingrum, Widianingrum (Fakultas Peternakan Universitas Jambi, 2008)
The objective of the study was to evaluate the effect of concentrate feeding method and forage on PE male goat productivity. Research was conducted from October-December 2006 in Satuan Kerja Pembibitan Ternak Dinas Sumber Rejo, Kendal Regency. Research used 12 heads of post weaning PE goat with initial body weight of 16.56 ± 2.64 kg. Research used completely randomized design (CRD) with 3 treatments and 4 replications. The treatments were (A) goat given concentrate together with forage; (B) goat given concentrate and 2 hours afterward given forage; (C) goat given concentrate and 4 hours afterward given forage. Ratio consisting of concentrate and field grass was given twice a day, in the morning and afternoon. Drinking water was given ad libitum. Variable measured were dry matter (DM) consumption, average daily gain (ADG) and feed conversion. Result of the research showed that DM consumption, ADG and feed conversion in every treatment shown no significance (P >0.05) statistically. However, treatment B tended to have higher ADG and lower feed conversion quantitatively. Treatments A, B and C in succession showed ration consumption of 698.01; 735.20 and 727.81 g/head/day; ADG of 44.08; 46.28 and 43.31 g/head/day, and feed convertiont 15.84; 15.89 and 16.81.